On two new species of Schendylurus Silvestri 1907 from Venezuela, with redescription of S. colombianus Chamberlin 1921 and S. virgingordae Crabill 1960 (Chilopoda Geophilomorpha Schendylidae) - Pereira, Luis Alberto (1993)
Fil: Pereira, Luis Alberto. División Zoología Invertebrados. Facultad de Ciencias Naturales y Museo. Universidad Nacional de La Plata; Argentina